Deazaflavin reductive photocatalysis involves excited semiquinone radicals - Andreas Graml (Nature Portfolio, 2020)
Flavins and deazaflavins are well suited for photoredox processes but their application in photoreductions is challenging. Here, the authors provide direct evidence of the high reductive power of excited deazaflavin semiquinones and their application in catalytic photodehalogenations.